THE OFFER OF REHABILITATION CENTER EUROMED IN MIELNO ASAN EXAMPLE OF BRANDED PRODUCT OF MEDICAL TOURISM (Research Bulletins of the Faculty of Economic Sciences, 2021)
Touristbranded productsare among the mosteffectiveelements ofthe marketing mixof the region.In the case ofWest Pomeraniasuchbranded productis the offerof health tourism. This paper presents theopinions ofpatients andstaffabout the offerEuromedRehabilitation Center. Studies showthat the qualityis high and thetherapyis delivering the desiredresults.The company shouldconsolidateitsgood image.